2015
DOI: 10.1002/da.22450
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Executive Functioning in Pediatric Trichotillomania (Hair Pulling Disorder)

Abstract: Children with HPD performed more poorly on tasks of executive functioning as compared to controls. Correlational analyses suggest potentially distinct pathophysiology underlying automatic and focused pulling warranting further research. Limitations and future areas of inquiry are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…However, there were no group differences on the TSC-C Severity, F(1,17) = 0.68, p = .42, η 2 = .03, TSC-C Impairment, F(1,17)=.003, p = 0.957, η 2 = .00, TSC-C Total, F(1,17) = .41, p = 0.53, η 2 = .01, or TSC-P Impairment, F(1, 16) = 1.40, p = 0.253, η 2 = .04, at post-training. At baseline, there were no group differences on the indices of the SST: RT on Block 1, t (18) = .21, p = 0.84, RT on Block 2, t(18) = .1.15, p = 0.27, and overall commission errors, t (18) = .49, p = 0.63. In an ANCOVA controlling for commission errors at pre-training and the current RT, the RIT group made significantly fewer commission errors than the WLT group at posttraining, F(1,16) = 7.39, p = 0.015, η 2 = .30 (large effect).…”
Section: Self-and Parent-reported Symptom Scoresmentioning
confidence: 85%
“…However, there were no group differences on the TSC-C Severity, F(1,17) = 0.68, p = .42, η 2 = .03, TSC-C Impairment, F(1,17)=.003, p = 0.957, η 2 = .00, TSC-C Total, F(1,17) = .41, p = 0.53, η 2 = .01, or TSC-P Impairment, F(1, 16) = 1.40, p = 0.253, η 2 = .04, at post-training. At baseline, there were no group differences on the indices of the SST: RT on Block 1, t (18) = .21, p = 0.84, RT on Block 2, t(18) = .1.15, p = 0.27, and overall commission errors, t (18) = .49, p = 0.63. In an ANCOVA controlling for commission errors at pre-training and the current RT, the RIT group made significantly fewer commission errors than the WLT group at posttraining, F(1,16) = 7.39, p = 0.015, η 2 = .30 (large effect).…”
Section: Self-and Parent-reported Symptom Scoresmentioning
confidence: 85%
“…Moreover, one study only included children, which potentially increased sample heterogeneity since the cognitive differences between adult and child TTM patients are not known. 34 Both aforementioned studies also used pooled sample data, and it is unclear whether these samples were wholly discrete or included shared participants. It is possible that samples overlapped, resulting in a larger effect size.…”
Section: Discussionmentioning
confidence: 99%
“…14 It is thus difficult to compare these three disorders in terms of inhibition, because of the divergent findings in TTM. Second, altered flexibility was found in adults with OCD 12 (but not in children 13 ) and in TS, 15 but not in TTM 93,95,[97][98][99] (except in one study, which found a deficit in the Object Alternation task, but not in the Wisconsin Card Sorting Test [WCST] 100 ). Attention deficits are found in all three disorders, 12,101 but more mixed results are found in TS (some studies found a deficit, [102][103][104] whereas others did not [105][106][107] ).…”
Section: Neuropsychologymentioning
confidence: 99%
“…13 In TTM, no difference from controls was found. 97,100,108 In TS patients, some studies reported deficits 106,[109][110][111][112][113] while others did not. 114 Looking at these data, TTM seems closer to TS than to OCD.…”
Section: Neuropsychologymentioning
confidence: 99%